Swans of the Kremlin : Ballet and Power in Soviet Russia - Ezrahi, Christina (Book collections on Project MUSE., 2012)
"Classical ballet was perhaps the most visible symbol of aristocratic culture and its isolation from the rest of Russian society under the tsars. In the wake of the October Revolution, ballet, like all of the arts, fell under the auspices of the Soviet authorities. In light of these events, many feared that the imperial ballet troupes would be disbanded. Instead, the Soviets attempted to mold the former imperial ballet to suit their revolutionary cultural agenda and employ it to reeducate the masses. As Christina Ezrahi's groundbreaking study reveals, they were far from successful in this ambitious effort to gain complete control over art. Swans of the Kremlin offers a fascinating glimpse at the collision of art and politics during the volatile first fifty years of the Soviet period. Ezrahi shows how the producers and performers of Russia's two major troupes, the Mariinsky (later Kirov) and the Bolshoi, quietly but effectively resisted Soviet cultural hegemony dur.